Social and health factors associated with unfavourable treatment outcomes in children and adolescents with drug-sensitive tuberculosis in Brazil: a national retrospective cohort studyResearch in context - Victor Santana Santos; Jamile Rodrigues Cosme de Holanda; Ruy Dantas Silveira Gois-Neto; Ethel Leonor Noia Maciel; Fernanda Dockhorn Costa Johansen; José Nildo de Barros Silva-Júnior; Wesley Adson Costa Coelho Correio; José Roberto Lapa e Silva; José Rodrigo Santos Silva; Ricardo Queiroz Gurgel; Tom Wingfield (Elsevier, 2024)
Summary: Background: Although tuberculosis (TB) poses a significant global health threat to children and adolescents, there is limited information on the factors associated with TB treatment outcomes in this group. This study investigated the social and health factors associated with unfavourable treatment outcomes in children and adolescents with TB in Brazil, a high TB burden country. Methods: We conducted a population-based national retrospective cohort study of children (0-9 years) and adolescents (10-17 years) with TB in Brazil notified to the national Sistema de Informação de Agravos de Notificação (Sinan) from Jan 1, 2001, to Dec 31, 2022. Unfavourable treatment outcomes were defined as loss to follow-up, treatment failure, and death. Logistic regression and multinomial models examined the association between social and health factors, unfavourable treatment outcomes overall, and loss to follow-up and death, respectively. Findings: A total of 88,270 children and adolescents with TB were included of whom 25,600 (30.6%) had healthcare worker-supervised directly observed therapy (DOT). Of these, 9303 (10.5%) individuals experienced unfavourable TB treatment outcomes. For children, HIV infection (adjusted Odds Ratio 2.4, 95% confidence interval 1.9-3.1) and did not receive DOT (2.3, 1.9-2.7) were associated with unfavourable treatment outcomes. For adolescents, alcohol use (1.6, 1.2-2.0), illicit drug use (4.2, 3.4-5.1), tobacco use (1.6, 1.3-2.1), HIV infection (2.7, 2.2-3.4), and not receiving DOT (2.6, 2.3-2.9) were associated with unfavourable TB treatment outcome. Receiving social protection through government cash transfers protected against death (0.5, 0.3-0.9). Interpretation: In Brazil, TB treatment success rates were comparable to WHO End TB Strategy targets (90%). Substance use, HIV infection, and the absence of supervised treatment were the main factors associated with unfavourable treatment outcomes. Strategies to improve equity of TB treatment outcomes in this vulnerable group, including integrated HIV-TB services, DOT in healthcare facilities or communities, and holistic, person-centred healthcare and social protection, should be evaluated. Funding: Department of Health and Social Care (DHSC), the Foreign, Commonwealth & Development Office (FCDO), the Medical Research Council (MRC) and Wellcome, UK.